Literasi Gizi pada Anak Usia 5-6 Tahun Melalui Kegiatan Market Day di Tk Nasional Salomo - Lestari, Trifena Eva Dwi; Anita Chandra; Nila Kusumaningtyas (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
Unhealthy eating habits among early childhood children are a critical issue requiring educational intervention. This study examines the effectiveness of Market Day activities as a contextual learning method to enhance nutrition literacy in children aged 5–6 at TK Nasional Salomo. Nutrition literacy is defined as a child's ability to understand, recognize, and choose healthy foods. A descriptive qualitative approach was employed, with 26 children (Groups A and B) and their teachers as subjects. Data were collected through observation, interviews, and documentation. The findings indicate that Market Day significantly boosted children's enthusiasm for recognizing healthy foods, understanding their benefits, and making nutritious food choices. The active roles of teachers and parental support were identified as key success factors. This activity was proven effective in instilling nutrition literacy values from an early age, and its findings recommend the continued development of real-world, experience-based learning methods.